2018
DOI: 10.1007/s00442-018-4271-7
|View full text |Cite
|
Sign up to set email alerts
|

Northward expanding resident species benefit from warming winters through increased foraging rates and predator vigilance

Abstract: Species distributions shift northwards due to climate change, but the ecological mechanisms allowing range expansions are not fully understood. Most studies have concentrated on breeding seasons, but winter warming may also be important. Wintering distributions are restricted by food availability and temperature, which may also interact. Foraging in cold conditions requires adaptations as individuals have to be efficient in foraging, while staying warm and vigilant for predators. When the ambient temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…, Pakanen et al. ). In support of this, we found that birds were more likely to be detected at feeders during periods of more favorable (warmer, drier) weather conditions, suggesting greater use of supplemental feeding stations on mild, precipitation‐free days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Pakanen et al. ). In support of this, we found that birds were more likely to be detected at feeders during periods of more favorable (warmer, drier) weather conditions, suggesting greater use of supplemental feeding stations on mild, precipitation‐free days.…”
Section: Discussionmentioning
confidence: 99%
“…This may be especially true during extremely cold weather when the energy costs of foraging may outweigh the potential energy gains, resulting in an increased likelihood of energy shortfall (Brittingham and Temple 1988). On the other hand, if birds could fully meet their daily energy requirements, being partially determined by short-term fluctuations in minimum temperatures, they could minimize their longer-term risk of starvation by foraging more intensively when weather conditions become more favorable (Turcotte and Desrochers 2008, Vill en-P erez et al 2013, Pakanen et al 2018. In support of this, we found that birds were more likely to be detected at feeders during periods of more favorable (warmer, drier) weather conditions, suggesting greater use of supplemental feeding stations on mild, precipitation-free days.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic factors might impact the distribution and range shift of wintering bird species [36,37], especially the southerly distributed species, such as the Eurasian Tree Sparrow. For example, according to Burnett [33] the non-native Eurasian Tree Sparrow has extent of a great northward range expansion in USA, and Graham et al [73] suggested that under projected climate change scenarios, the distribution and range of the non-native Eurasian Tree Sparrow will increase markedly in the USA in the near future.…”
Section: Sparrow Populations Growth Rates In Finlandmentioning
confidence: 99%
“…However, for example, Mohring et al [69] did not detect influences of weather conditions for the House Sparrow population changes in Paris during 2003-2017. Additionally, our data collected during 1991-2020 does not give any indication that climatic change would have influenced the growth rates of the two sparrow species, even if we conducted our study in northern latitudes where climatic factors are estimated to be important factor affecting bird populations in natural habitats [36,37]. However, the positive population growth rate of the House Sparrow was observed in some northern study sites, and population increase in the Eurasian Tree Sparrow seems to be greater in the north than in the south.…”
Section: Sparrow Populations Growth Rates In Finlandmentioning
confidence: 99%
See 1 more Smart Citation